External validation of the Cardiff model of information sharing to reduce community violence: natural experiment. Issue 12 (26th November 2012) - Boyle, Adrian A; Snelling, Katrina; White, Laura; Ariel, Barak; Ashelford, Lawrence
Abstract : Background: Community violence is a substantial problem for the NHS. Information sharing of emergency department data with community safety partnerships (CSP) has been associated with substantial reductions in assault attendances in emergency departments supported by academic institutions. We sought to validate these findings in a setting not supported by a public health or academic structure. Methods: We instituted anonymous data sharing with the police to reduce community violence, and increased involvement with the local CSP. We measured the effectiveness of this approach with routinely collected data at the emergency department and the police. We used police data from 2009, and emergency department data from 2000. Results: Initially, the number of assault patients requiring emergency department treatment rose after we initiated data sharing. After improving the data flows, the number of assault patients fell back to the predata-sharing level. There was no change in the number of hospital admissions during the study period. There were decreases in the numbers of violent crimes against the person, with and without injury, recorded by the police. Conclusions: We have successfully implemented data sharing in our institution without the support of an academic institution. This has been associated with reductions in violent crime, but it is not clear whether this association is causal.